Overview on the Biochemical Potential of Filamentous Fungi to Degrade Pharmaceutical Compounds - Olicón-Hernández, Darío R.; González-López, Jesús; Aranda, Elisabet (Frontiers in Microbiology, 2017)
Pharmaceuticals represent an immense business with increased demand due to intensive livestock raising and an aging human population, which guarantee the quality of human life and well-being. However, the development of removal technologies for these compounds is not keeping pace with the swift increase in their use. Pharmaceuticals constitute a potential risk group of multiclass chemicals of increasing concern since they are extremely frequent in all environments and have started to exhibit negative effects on micro- and macro-fauna as well as on human health. In this context, fungi are known to be extremely diverse and poorly studied microorganisms despite being well suited for bioremediation processes, taking into account their metabolic and physiological characteristics for the transformation of even highly toxic xenobiotic compounds. Increasing studies indicate that fungi can transform many structures of pharmaceutical compounds, including anti-inflammatories, β-blockers, and antibiotics. This is possible due to different mechanisms in combination with the extracellular and intracellular enzymes, which have broad of biotechnological applications. Thus, fungi and their enzymes could represent a promising tool to deal with this environmental problem. Here, we review the studies performed on pharmaceutical compounds biodegradation by the great diversity of these eukaryotes. We examine the state of the art of the current application of the Basidiomycota division, best known in this field, as well as the assembly of novel biodegradation pathways within the Ascomycota division and the Mucoromycotina subdivision from the standpoint of shared enzymatic systems, particularly for the cytochrome P450 superfamily of enzymes, which appear to be the key enzymes in these catabolic processes. Finally, we discuss the latest advances in the field of genetic engineering for their further application.